Determination of learning needs of hospital myocardial Infarction patients and its relation with demographic data - Zahra Farzanegan (Iran University of Medical Sciences, 1998)
This is a field study to determine the learning needs of hospitalized myocardial infarction (M!) patients, about activity, exercise, diet, medications, follow-up and recurrence predisposing factors, and their relation with demographic data in these patients, when they were discharged from cardiac unit. The study population comprised 92 randomly selected MI patients (77 men,26 women) on discharge time from the cardiac units of Iran University educational hospitals in Tehran. One set of data was collected and the tool was a two part questionnaire developed by the researcher consisting of two parts. The first part included 5 questions on subject demographic data and the second consisted of 32 questions on learning needs of patients. The collected data is presented in 40 tables and the descriptional and inferential statistics were used to analyze them. The findings of investigation showed that the men age of the subjects was 58.5 years. The majority of subjects was male, illiterate and married. 50% of subjects were employed. The statistical test showed there was a meanful significant correlation between all of the demographic variables of sample except of age and subject's learning needs such as activity. There was a significant correlation between the demographic variables of the sample such as age  with job satisfaction factors and managers function and managers function and the average for social dysfunction with nurses mental health, in comparison with other factors, were consideraly high. Path analysis was applied, and a meaningful and direct correlation between nursing service managers and hospital's manager, on one hand, and an indirect correlation with nurses stress, on the other hand were obtained. Based on the findings, some recommendations for future studies and application of the [mdings were made.